Makna Simbolik Kepemimpinan Melayu dalam Lagu 'Lancang Kuning': Kajian Analisis Wacana Kritis Model Fairclough - Isnaini, Faizzatin; Mahliatussikah, Hanik (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
Lancang Kuning is one of the Malay cultural heritages that embodies values of leadership. As part of oral tradition, this song serves not only as entertainment but also as a medium for conveying social and moral messages. This study aims to analyze the meaning of leadership in Malay culture as reflected in the lyrics of Lancang Kuning using Norman Fairclough’s Critical Discourse Analysis (CDA) model. The method employed is qualitative descriptive with text analysis and literature review techniques. The analysis follows Fairclough’s three-dimensional framework: (1) textual analysis, which explores the language structure, metaphors, and symbolism in the lyrics; (2) discursive practice analysis, which examines how the song is used within Malay society to reinforce leadership values; and (3) social practice analysis, which investigates the relevance of the song in the context of contemporary Malay leadership. The findings reveal that Lancang Kuning represents an ideal form of leadership in Malay culture through the symbols of the helmsman as the leader, the rudder as policy, and the storm as challenges faced in leadership. The song emphasizes the importance of wise and knowledgeable leaders to ensure the ship (society) does not sink into uncertainty. The main contribution of this study lies in its reinforcement of discourse studies by highlighting oral cultural heritage as a form of social construction that conveys local leadership values. Furthermore, the research enriches the understanding of leadership dynamics in Malay culture and opens space for further exploration of cultural texts as reflections of a society’s social and ideological structures.